Understanding Technology in Birth Care from the Experiences of Taiwanese Obstetricians. Issue 1 (1st March 2020) - Kuan, Chen-I
Abstract: Childbirth in Taiwan is characterized by the use of intensive technological and surgical interventions. Taiwanese cesarean rates are among the highest in the world, fetal monitoring is standard, and interventions such as episiotomy and labor augmentation are routinized practices during childbirth. In this Research Note, I describe the sociopolitical context that has given rise to this situation. More specifically, based on ethnographic research concerning birth care, I explore the ways obstetricians navigate this context and highlight the values and considerations that produce and shape "care" on the ground. I argue that understanding how interventionist birth care has come about, and how it is sustained as obstetricians manage care in daily practice, is vital to inform ongoing feminist activism for women's self-determination and the de-medicalization of childbirth in Taiwan.